2023
DOI: 10.1111/cge.14470
|View full text |Cite
|
Sign up to set email alerts
|

Identifying candidate genes underlying isolated congenital anosmia

Marissa L. Kamarck,
Casey Trimmer,
Nicolle R. Murphy
et al.

Abstract: An estimated 1 in 10 000 people are born without the ability to smell, a condition known as congenital anosmia, and about one third of those people have non‐syndromic, or isolated congenital anosmia (ICA). Despite the significant impact of olfaction for our quality of life, the underlying causes of ICA remain largely unknown. Using whole exome sequencing (WES) in 10 families and 141 individuals with ICA, we identified a candidate list of 162 rare, segregating, deleterious variants in 158 genes. We confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…ICA is a genetically heterogeneous disorder, with only nine implicated genes (CNGA2, TENM1, PROKR2, PROK2, FGFR1, SEM3A, CHD7, ANOS1, FGF8). A recently published study that used whole-exome sequencing in 10 families and 141 individuals with ICA confirmed the involvement of the CNGA2 gene as an essential component of the olfactory transduction pathway and further identified a loss-of-function variant in SREK1IP1, with a role in zinc ion binding, suggesting a potential influence on olfactory signaling [21].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…ICA is a genetically heterogeneous disorder, with only nine implicated genes (CNGA2, TENM1, PROKR2, PROK2, FGFR1, SEM3A, CHD7, ANOS1, FGF8). A recently published study that used whole-exome sequencing in 10 families and 141 individuals with ICA confirmed the involvement of the CNGA2 gene as an essential component of the olfactory transduction pathway and further identified a loss-of-function variant in SREK1IP1, with a role in zinc ion binding, suggesting a potential influence on olfactory signaling [21].…”
Section: Introductionmentioning
confidence: 81%
“…Anosmia can thus be related to dementia, such as in Parkinson's or Alzheimer's disease, or it can be present at birth (congenital) or of unknown cause (idiopathic) [20]. The underlying causes of congenital anosmia, which can be syndromic (part of a syndrome, such as Kallmann syndrome) or nonsyndromic (isolated congenital anosmia, ICA), remain largely unknown [21]. ICA is a genetically heterogeneous disorder, with only nine implicated genes (CNGA2, TENM1, PROKR2, PROK2, FGFR1, SEM3A, CHD7, ANOS1, FGF8).…”
Section: Introductionmentioning
confidence: 99%
“…Human SREK1IP1 has also been identified as an interactor of METHYLTRANSFERASE LIKE 16 (METTL16; Covelo-Molares et al, 2021), one of the two enzymes that catalyze the deposition of N 6 -methyladenosine (m 6 A) epitranscriptomic marks onto mRNAs and U6 small nuclear RNA (snRNA) (Warda et al, 2017). Dominant frameshift alleles of SREK1IP1 have been associated with congenital anosmia (Kamarck et al, 2024).…”
Section: Introductionmentioning
confidence: 99%